Impact of Ferric Chloride–Induced Oxidation on the Physicochemical Characteristics of Chicken Fat and Its Biodiesel - Chaleb P. Maanari; Sanusi Gugule; Feti Fatimah; Stefan M. Rumengan; Aisyiah R. P. Utami; Mustapa Mustapa; Indah U. Br. Sidabukke (Jurnal Akademika Kimia, 2026)
Background/problems: Biodiesel from animal fats is vulnerable to metal-catalyzed oxidation that degrades fuel quality because of the unsaturated fatty acid content. This study investigates the oxidative stability and physicochemical changes of chicken fat and its biodiesel upon FeCl₃-catalyzed oxidation. Methods: Chicken fat was transesterified to produce biodiesel; chicken fat (CF) and chicken-fat biodiesel (CF-BD) were then subjected to an FeCl₃ oxidative condition. Acid value (AV), iodine value (IV), peroxide value (PV), kinematic viscosity at 40 °C, and density were determined using standard titrimetric and physical methods; FTIR assessed spectral changes. ANOVA compared group means. Findings: Oxidation significantly increased AV and PV for both matrices, with a marked PV rise in CF-BD (6.17 ± 0.29 to 88.17 ± 5.35 meq/kg), and decreased IV (CF-BD 84.30 ± 4.51 to 48.70 ± 4.32 g I₂/100 g). Viscosity and density increased modestly. Visually, CF-BD shifted from clear yellow-green to brown and turbid with sediment, consistent with polymer formation and methyl-ester degradation. FTIR showed attenuation/shift of ester carbonyl and aliphatic bands. Conclusion: FeCl₃-induced oxidation measurably deteriorates CF-BD quality, breaching key limits in ASTM/SNI for acid value and viscosity. Impact: Results underscore the need to control trace metals and apply antioxidant/metal-deactivator strategies in storage and distribution, and validate the FeCl₃ assay as a practical accelerated-degradation model for stability and additive screening.